An asymmetric key-based security architecture for wireless sensor networks - Haque, Md. Mokammel; Pathan, Al-Sakib Khan; Hong, Choong Seon; Huh, Eui-Nam (Korea Society of Internet Information, 2008)
In spite of previous common assumptions about the incompatibility of public key cryptography (PKC) schemes with wireless sensor networks (WSNs), recent works have shown that they can be utilized for such networks in some manner. The major challenge of employing a PKC-based scheme in a wireless sensor network is posed by the resource limitations of the tiny sensors. Considering this sensor feature, in this paper we propose an efficient PKC-based security architecture with relatively lower resource requirements than those of previously proposed PKC schemes for WSN. In addition, our scheme aims to provide robust security in the network. Our security architecture comprises two basic components; a key handshaking scheme based on simple, linear operations and the derivation of a decryption key by a receiver node. Our architecture enables node-to-base-station and node-to-node secure communications. Analysis and simulation results show that our proposed architecture ensures a good level of security for network communications, and can be effectively implemented with the limited computational, memory, and energy budgets of current-generation sensor nodes.